2011
DOI: 10.3109/01480545.2010.538695
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of chlorophenoxy herbicide diclofop-methyl in micein vivoand in human lymphocytesin vitro

Abstract: Diclofop-methyl (DM) is a chlorophenoxy derivative used in large quantities for the control of annual grasses in grain and vegetable crops. In this study, the genotoxic effects of DM were investigated by measuring chromosomal aberrations (CAs) in mouse bone-marrow cells and CA and the comet assay in human peripheral lymphocytes. Mice were treated with 15.63, 31.25, 62.5, and 125 mg/kg body weight of DM intraperitoneally for 24 hours, and 15.63-, 31.25-, 62.5-, 125-, and 250-µg/mL concentrations were applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
1
13
0
1
Order By: Relevance
“…In positive control (100 μM H 2 O 2 ), the tail intensity was ranged from 55.25-56.96%. Similar to our data, Unal et al [3] found diclofop-methyl was a cyto-and genotoxic agent in human lymphocytes and mouse bone-marrow cells. They observed that a high degree of DNA damage was in lymphocytes from 6.00 ±0.75 to 12.79 ±1.22, respectively.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…In positive control (100 μM H 2 O 2 ), the tail intensity was ranged from 55.25-56.96%. Similar to our data, Unal et al [3] found diclofop-methyl was a cyto-and genotoxic agent in human lymphocytes and mouse bone-marrow cells. They observed that a high degree of DNA damage was in lymphocytes from 6.00 ±0.75 to 12.79 ±1.22, respectively.…”
Section: Resultssupporting
confidence: 81%
“…Aryloxy phenoxy propionic acid herbicides are one of the major pesticide groups. Diclofop-methyl is a selective, post emergence aryloxy phenoxy propionic acid herbicide primarily used to control wild oat (Avena fatua L.) and other annual graminaceous weeds in wheat, barley, and soybeans [3,17]. Exposure to some of these pesticides may lead to modifications in the genetic material thereby causing mutagenicity, carcinogenicity, teratogenicity and immunotoxicity [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CPF can induce toxicity and oxidative stress [22,23]. Experimental data revealed that pesticides such as cypermethrin may possess genotoxic, mutagenic, teratogenic, and carcinogenic properties, inducing mutations, chromosomal alterations, or DNA damage [24]. The prolonged and indiscriminate use of cypermethrin was reported to cause both acute and chronic toxicity in non-target species including humans [25].…”
Section: Biochemical Indicesmentioning
confidence: 99%